High-throughput drug screening identifies the ATR-CHK1 pathway as a therapeutic vulnerability of CALR mutated hematopoietic cells - Jia, Ruochen (Blood Cancer J, 2021)
Mutations of calreticulin (CALR) are the second most prevalent driver mutations in essential thrombocythemia and primary myelofibrosis. To identify potential targeted therapies for CALR mutated myeloproliferative neoplasms, we searched for small molecules that selectively inhibit the growth of CALR mutated cells using high-throughput drug screening. We investigated 89 172 compounds using isogenic cell lines carrying CALR mutations and identified synthetic lethality with compounds targeting the ATR-CHK1 pathway. The selective inhibitory effect of these compounds was validated in a co-culture assay of CALR mutated and wild-type cells. Of the tested compounds, CHK1 inhibitors potently depleted CALR mutated cells, allowing wild-type cell dominance in the co-culture over time. Neither CALR deficient cells nor JAK2V617F mutated cells showed hypersensitivity to ATR-CHK1 inhibition, thus suggesting specificity for the oncogenic activation by the mutant CALR. CHK1 inhibitors induced replication stress in CALR mutated cells revealed by elevated pan-nuclear staining for γH2AX and hyperphosphorylation of RPA2. This was accompanied by S-phase cell cycle arrest due to incomplete DNA replication. Transcriptomic and phosphoproteomic analyses revealed a replication stress signature caused by oncogenic CALR, suggesting an intrinsic vulnerability to CHK1 perturbation. This study reveals the ATR-CHK1 pathway as a potential therapeutic target in CALR mutated hematopoietic cells.